Pengaruh Diferensiasi Produk Terhadap Kepuasah Konsumen Pada UD Jaya Motor Ternate - Muhammad Hi Hasan (Peneliti.net, 2021)
This study aims to determine the level of consumer satisfaction with product differentiation policies at UD. Jaya Motor Ternate. The method used is simple regression method and correlation coefficient and t test to see the effect and relationship of product differentiation on consumer satisfaction. The data and data sources were obtained directly from the respondents by collecting data in the form of a questionnaire. primary data, the source of which is UD Jaya Motor Ternate using Multiple Linear Regression. The results showed that product differentiation has a strong relationship with consumer satisfaction at UD Jaya Motor Ternate. This is evidenced by the results obtained in hypothesis testing where the value of tcount = 13.29 > from ttable = 1.701 at = 0.05 or 5% and the value of the correlation coefficient of 0.929 and the value of the coefficient of determination = 86.3% then the simple regression equation obtained is y = 7.707 + 0.87106 x. This means that any decrease in product differentiation as 1% at Toko Jaya Motor Ternate will increase customer satisfaction by 0.87106%.